The Measurement of Customer Satisfaction Index with Method of Importance-Performance and Gap Analysis - Ahmad Syarif (Global Review of Islamic Economics and Business, 2019)
Customer satisfaction was the most talked topics in the service industry. Customer satisfaction is the main priority of the success of management of banking.  Banking was always innovating and training human resources in order to reduce the needs of customers. Researchers analyze whether the Bank's service is in compliance with the hopes of the customer. Research conducted at the Bank Syariah Mandiri Samarinda. This research utilized 450 respondents as samples and a Cartesian diagram as performance level. The result obtained (1) the existence of a cash machine were the important factors but management had not been fullest implement according to the wishes of the customer, (2) generally, the client was very satisfied over Bank Syariah Mandiri services, the average customer satisfaction above BSM performance with 97.36%.